2015
DOI: 10.1128/aem.01991-15
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Secretion of Indole-3-Acetic Acid and Its Morphological Effects on Tricholoma vaccinum-Spruce Ectomycorrhiza

Abstract: bFungus-derived indole-3-acetic acid (IAA), which is involved in development of ectomycorrhiza, affects both partners, i.e., the tree and the fungus. The biosynthesis pathway, excretion from fungal hyphae, the induction of branching in fungal cultures, and enhanced Hartig net formation in mycorrhiza were shown. Gene expression studies, incorporation of labeled compounds into IAA, heterologous expression of a transporter, and bioinformatics were applied to study the effect of IAA on fungal morphogenesis and on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 58 publications
2
73
0
1
Order By: Relevance
“…The hypothetical MATE transporter is encoded to mediate IAA efflux. Very recently, the MATE transporter Mte1 of the ectomycorrhizal fungus Tricholoma vaccinum was shown to export IAA during its compatible interaction with the host, positively regulating ectomycorrhiza formation and morphology [52]. Interestingly, some multidrug resistance-like genes of Arabidopsis have also been shown to transport IAA [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothetical MATE transporter is encoded to mediate IAA efflux. Very recently, the MATE transporter Mte1 of the ectomycorrhizal fungus Tricholoma vaccinum was shown to export IAA during its compatible interaction with the host, positively regulating ectomycorrhiza formation and morphology [52]. Interestingly, some multidrug resistance-like genes of Arabidopsis have also been shown to transport IAA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Trp is mostly used as a precursor of IAA, essentially by the IAM or IPA pathway [50]. While the pivotal role of this phytohormone in development of hyperplastic symptoms caused by Ustilago maydis and P. savastanoi on their hosts [51], or for rhizobia and ectomycorrhizal fungi in supporting their beneficial interaction with plants is very clear [52], its physiological role in the presence of IAA produced by plant pathogenic necrotrophic fungi such as Colletotrichum and Fusarium spp. is less intuitive [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Uncultured bacteria are also quite common in hostassociated environments, and mixed cultures can offer a chance to study host−microbe interactions (Stewart 2012, Krause et al 2015. For example, cocultures of algae and bacteria revealed that 2 specific bacterial strains (originally identified as Roseobacter sp.…”
Section: Studying Biochemical and Ecological Interactionsmentioning
confidence: 99%
“…Plant-derived phytohormones were shown to increase growth and hyphal ramification in T . vaccinum , and the fungus is able to produce indole-3-acetic acid [8, 15]. …”
Section: Introductionmentioning
confidence: 99%